Pelatihan Pengembangan Soal Matematika Tipe HOTS untuk Kemampuan Berpikir Kritis Matematis di SMP Bunda Kandung Jakarta Selatan - Mahyudi Yudi; Indra Kurniawan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The development of progress in the world of education, especially mathematics, requires reliable students who are not only able to solve mathematical problems. However, they can further develop their higher order thinking skills, such as creative, critical and reasoning thinking. These abilities must be continuously honed and trained by familiarizing students with questions that do not only remember. Students should be able to develop their mathematical literacy by working on HOTS (higher order thinking skill) questions. Currently we are entering the digital era known as the industrial revolution 4.0, in the 21st century the challenges and competition in the future will be very tight. There are four skills needed in the 21st century, known as the 4Cs, namely communication, collaborative, critical thinking, and creativity. The use of Higher Order Thinking Skills (HOTS) questions as a learning instrument is an effort to improve students' critical thinking skills as one of the skills needed in the 21st century.